GRAND DESIGN OF TRANGSAN RATTAN TOURISM VILLAGE DISTRICT SUKOHARJO, CENTRAL JAVA - Mulyadi, Mulyadi; Sarjiyanto, Sarjiyanto (Universitas Negeri Semarang, 2019)
Trangsan is the largest producer of rattan handicrafts in Central Java and number 2 in Indonesia. It contributes to increase revenue through export taxes and foreign exchange. Rattan was the second largest contributor to exports of Solo Raya after textiles. Trangsan is a village in Sukoharjo district which has a unique, specific, and historical. The village layout is very strategically and located at the intersection of three major cities (Solo - Yogyakarta - Semarang), and at the crossing of mass transportation. This scientific paper will be the basis for designing Trangsan rattan for being the Tourism Village. Starting from this Grand Design, then expected to be one of the tourist destinations in Sukoharjo. Grand Design approach adopted institutional capacity building combined with the pattern of empowerment in the industrial district. Promotion approach through information technology and governance approach is intended to bring the partnership to ensure the sustainability. Grand Design arranged followed by the inauguration of the first step the establishment of a tourist village (Launching). The next stage is the preparation of a global media campaign with the creation of websites for marketing the tourist village of rattan. Segmentation of the market today is the foreign buyer, but must be followed up with the creation of products for the domestic market that are easy to carry visitors this tourist village.